The reestablishment of civil power in the Irish Free State through the overcoming of the Army Mutiny and the work of the Army Inquiry Committee 1924. - Price, Dominic Anthony (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2026)
This thesis presents a detailed examination of the Army Inquiry Committee which took place from April to June 1924. The Army Inquiry Committee was commissioned by the Executive Council of the Free State to determine the causes of the Army Mutiny of March 1924. The research carried out reveals what caused the Mutiny and most importantly, how civil power was re-established and the Irish Free State in 1923 and 1924. This thesis is the first historical in-depth study undertaken into the complete Army Inquiry Committee Papers and the supporting files in the Department of Defence A Files collections at the Military Archives of Ireland. As such, this document explores many themes which earlier historians were unable to examine and in doing so provides a clearer understanding of not just an Army Mutiny but an Army Crisis which placed the existence of freedom and democracy in the Free State in danger. The threat posed to the State came primarily from the presence of secret societies in the Army and the body politic. The existence of such secret societies served to undermine discipline and cohesion within the Army and also within the Government Party, Cumann na nGaedheal. The analysis undertaken into the Army Inquiry Committee Papers and the Department of Defence A Files revealed the complexity of establishing civil authority after a decade of military law and extensive military presence throughout what became the Free State. Presented in this thesis are the major roles played by senior Army officers, the President and Government ministers, politicians, the civil service and the judiciary as they struggled to shape the nature of government and political direction of the State. This thesis also examines the role played by civic society which placed serious pressure on the Government and the Army to restore civil rule. In conclusion, this thesis examines the solutions to the Army Crisis which evolved from the work of the Army Inquiry Committee and the witnesses who presented themselves before the Inquiry. This thesis challenges the view of the Army Mutiny as a minor event with little or no consequences for civil liberty and democracy.
APPROVED
Keywords: Irish Free State; Army Mutiny; Democracy; Óglaigh na hÉireann; I.R.B.; Irish Republican Brotherhood; I.R.A.O.; Irish Republican Army Organisation; Dáil Éireann; 1924; W.T. Cosgrave; James Creed Meredith; Kevin O'Higgins; Richard Mulcahy; Seán Ó Murthuile; Gearoid O'Sullivan; Sean MacMahon; Jephson Byrne O'Connell; Dáil; Free State; Saorstt ireann; Saorstat Eireann; Denis J. Gorey; Gerald Fitzgibbon; Patrick McGilligan; Bryan Cooper; Civil authority; civic power; 1923; Army reform; civil service; Department of Defence; Army Finance Office; Military Archives; Army Crisis 1924; Demobilisation; Army discipline; Army allegiance; Army oath; Army Inquiry Committee Report; Irish History; Irish Free State History; British Commonwealth Democracy; Irish democracy; Freedom; Army Mutiny Inquiry; National Army